2006
DOI: 10.1007/s10126-006-6076-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Mapping of Amplified Fragment Length Polymorphism Markers Linked to Shell Color in Bay Scallop, Argopecten irradians irradians (Lamarck, 1819)

Abstract: Amplified fragment length polymorphisms (AFLP) were used to study the inheritance of shell color in Argopecten irradians. Two scallops, one with orange and the other with white shells, were used as parents to produce four F(1) families by selfing and outcrossing. Eighty-eight progeny, 37 orange and 51 white, were randomly selected from one of the families for segregation and mapping analysis with AFLP and microsatellite markers. Twenty-five AFLP primer pairs were screened, yielding 1138 fragments, among which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…For instance, QTL mapping for growth traits and disease resistance has been conducted in the Pacific oyster2829; QTL mapping for growth and shell colour has been conducted in Argopecten irradians 3031; and QTL mapping for growth traits and sex-determination has been conducted in Chlamys farreri 7. In addition, for some pearl mussels, QTLs have been identified for growth and shell colour in the freshwater mussel H. cumingii 32, and QTLs for pearl quality and shell growth have been identified in Pinctada maxima 3334.…”
mentioning
confidence: 99%
“…For instance, QTL mapping for growth traits and disease resistance has been conducted in the Pacific oyster2829; QTL mapping for growth and shell colour has been conducted in Argopecten irradians 3031; and QTL mapping for growth traits and sex-determination has been conducted in Chlamys farreri 7. In addition, for some pearl mussels, QTLs have been identified for growth and shell colour in the freshwater mussel H. cumingii 32, and QTLs for pearl quality and shell growth have been identified in Pinctada maxima 3334.…”
mentioning
confidence: 99%
“…The shell color was determined according to the color system developed by Elek and Adamkewicz [32] in this study. As previous studies indicated that shell color in the bay scallop is under single-gene control where white color is recessive [33], [34], the genotypes for orange-colored and white-colored parent were recorded as heterozygote and homozygote respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This can significantly reduce the cost of producing breeding lines and can accelerate the breeding program greatly. Several genetic markers associated with shell color have been identified in aquaculture species such as bay scallop (Qin et al 2007), Pacific lion-paw scallop (Petersen et al 2012), and noble scallop (Yuan et al 2012). A SCAR marker which was well correlated with Pacific oyster shell pigmentation of light and dark was also identified, suggesting a major locus that is responsible for foreground pigmentation (Ge et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…The amplified fragment length polymorphism (AFLP) technique is a powerful marker system (Vos et al 1995), which has been used extensively for linkage mapping and gene/QTL mapping in marine organisms (Yu and Guo 2003;Qin et al 2007;Guo et al 2012;Yuan et al 2012). The bulked segregant analysis (BSA), developed by Michelmore et al (1991), has been proved to be an effective method for detecting markers that are tightly linked with genes in many aquatic species (Nakamura et al 2001;Araneda et al 2005Araneda et al , 2009Felip et al 2005;Liu et al 2011;Ge et al 2014;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 98%